Studi Literatur Pengaruh Penambahan Bakteri Asam Laktat dalam Pakan Formulasi Lokal atau Pakan Komersial Terhadap Profil Mikrobiota Escherichia coli Saluran Pencernaan Ayam Broiler - Yolanda H.L Kabosu; Frans U Datta; Annytha I.R Detha (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Broiler chicken is a type of poultry that has a very fast growth rate, and it can be harvested at the age of 5 weeks. Meanwhile, to improve development and promote good health, commercial feed contains antibiotics that are often given by farmers as additives which can kill microbes. Therefore, lactic acid bacteria can be classified as probiotic and also serve as an alternative to be added to feed because of their effectiveness in low acid or pH. In fact, they kill the pathogenic microorganism Escherichia coli that causes colibacillosis. Therefore, this study aimed to determine the effect of adding lactic acid bacteria in local formulation or commercial feeds on the profile of Escherichia coli the digestive tract of broiler chicken. The literatures used for this study were obtained from searching and collection of various reference sources using Mendeley and Google Scholar applications. Based on literature study with several literature, it was found that the provision of liquid lactic acid bacteria and solid probiotics mixed with commercial or local feed formualtion can reduce the number of Escherichia coli. Furthermore, it increases body weight gain, egg production and availabilty of metabolic energy, cause high fiber digestion, as well as improve feed consumption and conversion. In addition, it increases intestinal villi in the duodenum, jejenum and ileum, as well as dilate villi in the ileum.